Optimizing TikTok and Instagram to Gain Election Voter Support in Ubung Kaja Village - Pancane, I Wayan Dikse; Suriana, I Wayan; Adrama, I Nyoman Gede (PT FORMOSA CENDEKIA GLOBAL, 2024)
Elections are a general voting process conducted by the people to choose leaders and representatives who will govern the country. But it is also often considered as the generation that is most indifferent to political issues and does not want to take advantage of the right to vote in elections. Instagram is a photo and video sharing application that also has similar features to Tiktok, such as Stories, Reels and IGTV. According to data published by the website We are Social - Hootsuit in February 2022, out of Indonesia's population of 277.7 million people, there are 191.4 million people who actively use social media with a percentage of 68.9%. Through the implementation of election marketing strategies in the era of social media, there have been positive changes in the understanding, awareness, and participation of the Ubung Kaja village community. It is hoped that these improvements can have a positive impact on the democratic process and result in more inclusive and representative elections